The Influence Of Supporting Celebrities (@Niniramadani06) on Consumer Loyalty Ms Glow Samarinda - Nahda, Hanifah; Hairunnisa, Hairunnisa (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
This study employs a purposive sampling method and non-probability sampling techniques for its quantitative approach to sampling. This study used 345 respondents who are MS Glow Samarinda customers and follow the Instagram account @Niniramadani06. Analytical techniques include straightforward linear regression analysis. Using the SPSS 28 application, testing the hypothesis with a partial test (t test). Based on the analysis and discussion, the celebrity @Niniramadani06 has a significant impact on MS Glow Samarinda's customer loyalty. Consumer loyalty is higher when the supporting celebrities are of higher quality. This study used 345 respondents who are MS Glow Samarinda customers and follow the Instagram account @Niniramadani06. Analytical techniques include straightforward linear regression analysis. Using the SPSS 28 application, testing the hypothesis with a partial test (t test). Based on the analysis and discussion, the celebrity @Niniramadani06 has a significant impact on MS Glow Samarinda's customer loyalty. Consumer loyalty is higher when the supporting celebrities are of higher quality. Based on the analysis and discussion, the celebrity @Niniramadani06 has a significant impact on MS Glow Samarinda's customer loyalty. Consumer loyalty is higher when the supporting celebrities are of higher quality. Based on the analysis and discussion, the celebrity @Niniramadani06 has a significant impact on MS Glow Samarinda's customer loyalty.